A mixed-methods investigation of health professionals' perceptions of a physiological track and trigger system. Issue 9 (9th October 2015) - Lydon, Sinéad; Byrne, Dara; Offiah, Gozie; Gleeson, Louise; O'Connor, Paul
Abstract : Background: Physiological track and trigger systems (PTTSs) regulate the monitoring of patients' vital signs and facilitate the detection and treatment of deteriorating patients. These systems are widely used, although compliance with protocol is often poor. Objective: This study aimed to examine the perceptions of a national PTTS among nurses and doctors and to identify the variables that impact on intention to comply with protocol. Methods: A mixed-methods research design was employed. During the initial qualitative phase, 30 hospital-based nurses and doctors participated in a series of semistructured interviews. During the subsequent quantitative phase, 215 nurses and doctors (24.1% response rate) responded to a questionnaire designed to assess attitudes towards the PTTS and factors that influence adherence to protocol. Results: Interview data revealed largely positive attitudes towards the PTTS but highlighted a number of barriers to its implementation and indicated that it is sometimes a source of tension between doctors and nurses. Quantitative data confirmed the validity of these findings, although nurses appeared to have more positive attitudes towards, and to perceive fewer barriers to, the usage of PTTS than were reported by the participating doctors. Conclusions: These findings reveal that non-compliance with PTTS protocol is unlikely to be attributable to negative perceptions of PTTSs. Instead, there are a number of barriers to the implementation of the system. These findings suggest that interprofessional training in PTTSs is essential while increased support for PTTS implementation among senior doctors would also yield improved adherence to protocol.